Effect of machining-induced surface residual stress on initiation of stress corrosion cracking in 316 austenitic stainless steel. (July 2016) - Zhang, Wenqian; Fang, Kewei; Hu, Yujin; Wang, Siyang; Wang, Xuelin
Highlights: SCC induced by machined surface residual stress in boiling MgCl2 was tested. SCC micro-crack density was evaluated as a function of machined residual stress. A strong correlation between residual stress and SCC micro-crack density was observed. There exists a critical residual stress for SCC micro-crack initiation. Abstract: The effect of machining-induced surface residual stress on the stress corrosion cracking (SCC) initiation in 316 stainless steel was investigated in boiling magnesium chloride solution. The crack density was used to evaluate the SCC initiation and propagation at different residual stress levels. The results showed a strong correlation between the residual stress and the resultant micro-crack density. When the residual stress reached a critical value, the micro-crack density increased significantly in the very early phase, and the critical stress is 190 MPa for 316 stainless steel. Additionally, the cracking behavior could be correlated with the machining effects on the surface layer.